Tradeoff between estimation performance and sensor usage in distributed localisation problems. (27th July 2006) - Liu, Juan; Huang, Qingfeng
In distributed sensor networks, the tradeoff between application performance and resource consumption is a fundamental issue. In this paper, we analyse the tradeoff in the context of localisation problems. In particular, the localisation performance is characterised using the Cramer-Rao lower bound which reflects the performance limit in the family of unbiased estimators. For a variety of distance-sensitive sensing models, the bound comes in closed-form. In view of the tradeoff, we design a circular incremental inclusion scheme for efficient sensor tasking and propose to use the theoretical Cramer-Rao lower bound as a guiding heuristic. Our results reveal that there is a performance limit for collaborative sensing, and the expansion of sensing group size incurs fast diminishing returns on performance. The study results in new insights and provides general guidelines for sensor tasking in practical applications.